Morphological, Pomological, and Nutritional Value of Wild and Cultivated Rosehip (Rosa canina L.) Genotypes in Slavonia, Croatia - Teuta Benković-Lačić; Božica Japundžić-Palenkić; Krunoslav Mirosavljević; Mario Rakić; Valentina Obradović; Matija Japundžić; Robert Benković (Acta Agrobotanica, 2022)
In this study, the morphological, pomological, and nutritional values of wild and cultivated rosehip fruits grown in the Slavonia region of eastern Croatia were studied. The results revealed significant differences in several morphological and pomological characteristics among the rosehip genotypes in terms of fruit weight, flesh weight, seed weight, and fruit flesh ratio, with no significant differences in fruit width, fruit length, fruit shape index, seed number per fruit, or seed length. The evaluated rosehip fruit genotypes differed significantly from each other in terms of hectoliter weight (kg), fruit bulk (cm3), and bulk density (kg/m3). For water–soluble extracts, ash, and pH, no statistical difference was found between naturally grown genotypes, but there was a significant difference between naturally grown and cultivated genotypes. Twenty-three major and trace elements were analyzed. The most abundant elements were K, Ca, Mg, and P in both cultivated and naturally grown fruits. The highest concentrations of microelements were Fe, Al, Mn, and Sr. The conventionally cultivated genotype L1 had the highest concentration of Fe and Na as essential elements for humans but also had the highest concentrations of Al, Sr, Ti, V, Cr, Pb, Co, Li, and As of all the genotypes studied. The naturally grown genotype L4 had the highest concentrations of S, Zn, Rb, and Cd and the lowest concentrations of Mg, K, and Ca among all studied genotypes. The data showed that the analyzed genotypes from eastern Croatia had good nutritional quality and variability, making them suitable as genetic resources and possibly leading to the detection of rosehip genotypes as potential sources of beneficial ingredients for human health.